Safety of midodrine in patients with heart failure with reduced ejection fraction: a retrospective cohort study - Wu, Ming-Ju; Chen, Cheng-Hsu; Tsai, Shang-Feng (Frontiers in Pharmacology, 2024)
Heart failure with reduced ejection fraction (HFrEF) poses significant health risks.Midodrine for maintaining blood pressure in HFrEF, requires further safety investigation. This study explores midodrine's safety in HFrEF through extensive matched analysis.Patients with HFrEF (LVEF <50%) without malignancy, non-dialysis dependence, or non-orthostatic hypotension, were enrolled between August 28, 2013, and August 27, 2023. Propensity score matching (PSM) created 1:1 matched groups. Outcomes included mortality, stage 4 and 5 chronic kidney disease (CKD), emergency room (ER) visits, intensive care unit (ICU) admissions, hospitalizations, and respiratory failure. Hazard ratios (HR) with 95% confidence intervals (95% CI) were calculated for each outcome, and Kaplan-Meier survival analysis was performed. Subgroup analyses were conducted based on gender, age (20-<65 vs. ≥65), medication refill frequency, and baseline LVEF.After 1:1 PSM, 5813 cases were included in each group. The midodrine group had higher risks of respiratory failure (HR: 1.16, 95% CI: 1.08-1.25), ICU admissions (HR: 1.14, 95% CI: 1.06-1.23), hospitalizations (HR: 1.21, 95% CI: 1.12-1.31), and mortality (HR: 1.090, 95% CI: 1.01-1.17). Interestingly, midodrine use reduced ER visits (HR: 0.77, 95% CI: 0.71-0.83). Similar patterns of lower ER visit risk and higher risks for ICU admissions, respiratory failure, and overall hospitalizations were observed in most subgroups.In this large-scale study, midodrine use was associated with reduced ER visits but increased risks of respiratory failure, prolonged ICU stays, higher hospitalizations, and elevated mortality in HFrEF patients. Further research is needed to clarify midodrine's role in hemodynamic support and strengthen existing evidence.Midodrine has been utilized for treating hypotension, particularly in patients with heart failure, albeit without confirmed safety. This large-scale study found that while midodrine use was linked to reduced emergency room visits, it also posed increased risks of respiratory failure, prolonged ICU stays, heightened hospitalizations, and elevated mortality among patients with heart failure with reduced ejection fraction (HFrEF). Therefore, considering both its advantages and disadvantages, the long-term usage of midodrine should be carefully assessed and justified.